2017
DOI: 10.1136/bjsports-2017-097792
|View full text |Cite|
|
Sign up to set email alerts
|

Serum androgen levels and their relation to performance in track and field: mass spectrometry results from 2127 observations in male and female elite athletes

Abstract: Female athletes with high fT levels have a significant competitive advantage over those with low fT in 400 m, 400 m hurdles, 800 m, hammer throw, and pole vault.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
99
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(110 citation statements)
references
References 35 publications
1
99
0
6
Order By: Relevance
“…The paper by Bermon and Garnier4 (funded by the IAAF and WADA) examined the results of endocrine variables in 1332 blood samples from elite female athletes who took part in the 2011 and 2013 IAAF World Athletic Championships; 17.3% of these athletes were sampled at both events.…”
Section: The Limitations Of a Cross-sectional Study Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The paper by Bermon and Garnier4 (funded by the IAAF and WADA) examined the results of endocrine variables in 1332 blood samples from elite female athletes who took part in the 2011 and 2013 IAAF World Athletic Championships; 17.3% of these athletes were sampled at both events.…”
Section: The Limitations Of a Cross-sectional Study Designmentioning
confidence: 99%
“…The hyperandrogenism rule concerns total endogenous blood testosterone, but Bermon and Garnier4 concentrated on the derived ‘free testosterone’ (fT) and found that there were five (of 21) events where athletes whose fT was in the highest tertile appeared to do better than those whose fT was in the lowest tertile. On the other hand, although not statistically significant, those with fT in the lowest tertile appeared to perform better than those in the highest tertile in nine events.…”
Section: The Limitations Of a Cross-sectional Study Designmentioning
confidence: 99%
“…The revised regulations are based largely upon a 2017 study that evaluated the influence of testosterone levels on athletic performance [64]. Bermon and Garnier [64] analyzed the performances of women at the 2011 and 2013 IAAF World Championships.…”
Section: Athletes and Hyperandrogenemiamentioning
confidence: 99%
“…Bermon and Garnier [64] analyzed the performances of women at the 2011 and 2013 IAAF World Championships. They divided the female competitors into 3 tertiles based on their free testosterone concentrations – low, medium, and high – then compared the high free testosterone tertile performances against the low free testosterone tertile performances.…”
Section: Athletes and Hyperandrogenemiamentioning
confidence: 99%
“…Bermon and Garnier1 summarised their recent findings by stating that in 5 of 21 events, ‘female athletes with high testosterone levels benefit from a 1.8% to 4.5% competitive advantage over other female competitors with normal androgen levels’. As the authors did not divide female athletes into comparison groups based on a value of free testosterone (fT) determined a priori to be ‘high’, the study’s design does not allow for this conclusion.…”
mentioning
confidence: 99%